An overview of waqf assets in Yemen: importance and challenges - Saad, Abdo Yousef Qaid; Mohammed, Mustafa Omar; Al-Jubari, Ibrahim (Gyandhara International Academic Publications, 2019)
Purpose of Study: Waqf has played a significant role throughout Islamic history. This has been possible through proper management, investment and financing of various Waqf assets to enhance the socioeconomic development of Muslim societies. In particular, it has contributed significantly to the encouragement of religious practices, improvement of education, health and helping the poor and the needy, creating employment and supporting other socio-economic activities. Methodology: The current study attempted to uncover these challenges facing by Waqf institution in Yemen. Particularly, issues such as management, investment and finance will be emphasized. Results: However, nowadays most of Waqf assets have become idle and no longer serves the needs of the Ummah due to problems, such as poor governance structure and human resource. Few studies have tried to address challenges facing Waqf but unfortunately these studies have been conducted in countries where the governance structure is robust and the quality of human resource is very good. Such models may not be suitable in contexts such as Yemen where Waqf assets are mostly in the form of physical assets such as lands and buildings and the quality of human resource and governance structure are poor